Recycling cellulose nanofibers from wood pulps provides drainage improvements for high strength sheets in papermaking. (20th August 2021) - Ang, Shaun; Ghosh, Debjani; Haritos, Victoria; Batchelor, Warren
Abstract: The recyclability of cellulose nanofibers (CNF) is one of its most promising features. However, the performance of recycled CNF is not fully established. In this work, we engineered CNF sheets from refined and homogenized industrial virgin pulp (BEK), industrial recycled pulp (DIP) and lab-scale recycled pulp (LRC). These original CNF sheets were then soaked and recycled using a standard disintegrator to produce recycled CNF sheets. The key changes with recycled CNF sheet properties were tracked and compared to their original CNF sheets. Fiber retention and sheet uniformity measurements revealed a higher proportion of fiber aggregates with original CNF from DIP and LRC, compared to BEK. The proportion of fiber aggregates increased even further with recycled CNF. These results are consistent with the well-established formation of strong irreversible hydrogen bonds which hinder complete refibrillation. The tensile index of original 10K1P (10, 000 PFI revolutions refined and 1 high-pressure homogenized pass) CNF sheets made from recycled DIP and LRC fibers at 110 Nm/g was only 10% lower compared to those made from virgin BEK fibers. Interestingly, all recycled CNF sheets from homogenized fibers successfully retained about 80% of their original CNF sheet strength. Remarkably, all recycled CNF sheets also had significant reductions in sheet drainage times, with the standout being the reduction from LRC 10K1P at 84 min to R-LRC 10K1P at 1.14 min of drainage time. The combination of high sheet strength and sharply reduced drainage times provide a rare example of the recycled product being superior to the original product. Graphical abstract: Image 1 Highlights: CNF produced from industrial virgin, industrial recycled and lab recycled pulp. Original and recycled CNF sheet strength, uniformity and drainage were compared. A higher amount of fiber aggregates is present in recycled CNF sheets. Recycled CNF sheets retained 80% of the original CNF sheet strength. Recycled CNF sheets had significant reductions in sheet drainage times.